E-Government in The Public Service Process at The Special Class I Immigration Office in Surabaya - Fadhlan Ginting S.; Fedianty Augustinah; Ulul Albab; Widyawati Widyawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze the implementation of e-Government in passport services at the Surabaya Special Class I Immigration Office and the opportunities and challenges in the implementation of e-Government at the office. The research method used is descriptive qualitative. Data collection techniques include interviews, observations, and documentation. The research informant is the Head of the Surabaya Special Class I Immigration Office. Data analysis techniques use the interactive model developed by Miles et al. (2014), namely data condensation, data presentation, and conclusion drawing. The results of the study show that the implementation of e-Government in passport services at the Surabaya Special Class I Immigration Office includes five main aspects: (a) complete telecommunication infrastructure, (b) adequate connectivity and use of information technology, (c) sufficient human resource readiness, (d) availability of funds and budget without issues, and (e) regulations and rules with legal force. Opportunities for e-Government at the Surabaya Special Class I Immigration Office include positive public response and accessibility to information technology. The challenges faced include cybercrime and the lack of awareness among some people about e-Government.